Is it possible to predict biological activity of any chemical, and if so, how? - Kurchii, B.A. (Фактори експериментальної еволюції організмів, 2010)
In this report we consider the role of several factors in the bioactivity/toxicity ofhormones, pesticides and pharmaceutical substances. It is concluded that taking intoaccount sterical factors, functional reactive groups and flanking substitutes is predictivetool in the prediction of bioactivity/toxicity of any given chemical.